Computational modeling for antiarrhythmic drugs for atrial fibrillation according to the genotypes. (24th May 2021) - Hwang, I; Park, J; Kwon, O; Lim, B; Hong, M; Kim, M; Yu, H; Kim, T; Uhm, J; Joung, B; Lee, M; Pak, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by a grant [HI19C0114] from the Ministry of Health and Welfare. Additionally, the work was funded by grants [NRF-2019R1C1C100907512], and [NRF-2020R1A2B01001695] from the Basic Science Research Program run by the National Research Foundation of Korea (NRF) under the Ministry of Science, ICT & Future Planning (MSIP). Background: The efficacy of antiarrhythmic drugs (AAD) can vary in patients with atrial fibrillation (AF) and the PITX2 gene affects the responsiveness of AADs. We explored the virtual AAD (V-AAD) responses between wild-type and PITX2+/- deficient AF conditions by realistic in-silico AF modeling. Methods: We tested the V-AADs in AF modeling integrated with patients' 3D-computed tomography and 3D-electroanatomical mapping, acquired in 25 patients (68% male, 59.8 ± 9.8 years old, 32.0% paroxysmal type). The ion currents for the PITX2+/- deficiency and each AAD (amiodarone, sotalol, dronedarone, flecainide, and propafenone) were defined based on previous publications. Results: We compared the wild-type and PITX2+/- deficiency in terms of the action potential duration (APD90), conduction velocity (CV), maximal slope of restitution (Smax), and wave-dynamic parameters, such as the dominant frequency (DF), phase singularities (PS), and AF termination rates according to the V-AADs. The PITX2+/- deficient model exhibited a shorter APD90 (p < 0.001), a lower Smax (p < 0.001), mean DF (p = 0.012), PS number (p < 0.001), and a longer AF cycle length (AFCL, p = 0.011). Five V-AADs changed the electrophysiology in a dose dependent manner. AAD-induced AFCL lengthening (p < 0.001) and reductions in the CV (p = 0.033), peak DF (p < 0.001) and PS number (p < 0.001) were more significant in PITX2+/- deficient than wild-type AF. PITX2+/- deficient AF was easier to terminate with class IC AADs than the wild-type AF (p = 0.018). Conclusions: The computational modeling-guided AAD test was feasible for evaluating the efficacy of multiple AADs in patients with AF. AF wave-dynamics and electrophysiological characteristics are different among the PITX2 deficient and the wild-type genotype models.